2019
DOI: 10.1111/acel.12995
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic signatures of Werner syndrome occur early in life and are distinct from normal epigenetic aging processes

Abstract: Werner Syndrome (WS) is an adult‐onset segmental progeroid syndrome. Bisulfite pyrosequencing of repetitive DNA families revealed comparable blood DNA methylation levels between classical (18 WRN‐mutant) or atypical WS (3 LMNA‐mutant and 3 POLD1‐mutant) patients and age‐ and sex‐matched controls. WS was not associated with either age‐related accelerated global losses of ALU, LINE1, and α‐satellite DNA methylations or gains of rDNA methylation. Single CpG methylation was analyzed with Infinium MethylationEPIC a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 45 publications
4
21
1
Order By: Relevance
“…POLD1, as the catalytic subunit of DNA polymerase delta and endowed with polymerase and exonuclease activities, plays a critical role in DNA synthesis and DNA repair processes ( Cui et al, 2019 ). Our previous study found that POLD1 expression was downregulated as cell aging in human lymphocytes and preliminarily confirmed that the expression of POLD1 was essential in cell cycle regulation and DNA damage repair processes ( Wang et al, 2012 ; Song et al, 2015 ; Maierhofer et al, 2019 ). However, the mechanism of age-related downregulation of POLD1 expression has not been fully explained.…”
Section: Introductionsupporting
confidence: 57%
“…POLD1, as the catalytic subunit of DNA polymerase delta and endowed with polymerase and exonuclease activities, plays a critical role in DNA synthesis and DNA repair processes ( Cui et al, 2019 ). Our previous study found that POLD1 expression was downregulated as cell aging in human lymphocytes and preliminarily confirmed that the expression of POLD1 was essential in cell cycle regulation and DNA damage repair processes ( Wang et al, 2012 ; Song et al, 2015 ; Maierhofer et al, 2019 ). However, the mechanism of age-related downregulation of POLD1 expression has not been fully explained.…”
Section: Introductionsupporting
confidence: 57%
“…In addition, the fact that several independent eEAAs were found to be significantly associated with Down's syndrome suggests that EAA is a multi-factorial composite trait. Our method also showed similar results for data on Werner's syndrome [16,24] (GSE131752), where the associations of Werner's syndrome with standard EAAs were found to be substantially weaker than those with eEAAs resulting from our PCbased method (PB<0.05, Figures S1 and S2, Additional file 2).…”
Section: Case 1: Extracted Eaas In Adults With Down'sand Werner's Synsupporting
confidence: 71%
“…This is in stark contrast with the increase during aging in global genomic DNA methylation in peripheral blood lymphocytes of healthy individuals and patients with Werner syndrome [Maierhofer et al, 2017;Horvath and Raj, 2018;Wang and Lemos, 2019]. In the latter syndrome, genes linked to transcription factor activity and sequencespecific DNA binding to promoters transcribed by RNA polymerase II were affected by differential methylation, which suggests that dysregulation of mRNA transcription may contribute to this syndrome [Maierhofer et al, 2019]. In contrast, RNA polymerase I rDNA transcription rates are not affected by differential methylation or loss of rDNA copies during aging [Malinovskaya et al, 2018].…”
Section: Impact Of Robertsonian Translocationsmentioning
confidence: 74%